2022
DOI: 10.1063/5.0071786
|View full text |Cite
|
Sign up to set email alerts
|

Testing the performance of secondary anvils shaped with focused ion beam from the single-crystal diamond for use in double-stage diamond anvil cells

Abstract: The success of high-pressure research relies on the inventive design of pressure-generating instruments and materials used for their construction. In this study, the anvils of conical frustum or disk shapes with flat or modified culet profiles (toroidal or beveled) were prepared by milling an Ia-type diamond plate made of a (100)-oriented single crystal using the focused ion beam. Raman spectroscopy and synchrotron x-ray diffraction were applied to evaluate the efficiency of the anvils for pressure multiplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This is actually a method that is widely used on large volume WC anvils [64]. The shape of the toroidal anvil has some similarities to the ds-DAC, as mentioned in the work of Dewaele et al and Khandarkhaeva et al tested several FIB machined toroidal anvils as second-stage anvils for the ds-DAC and concluded that the toroidal anvil showed greater stability in the assembly and more uniform pressure distribution in the sample cavity [65]. This result highlights the role of the T-DAC toroidal shape at high pressure and confirms its positive contribution.…”
Section: T-dacmentioning
confidence: 97%
“…This is actually a method that is widely used on large volume WC anvils [64]. The shape of the toroidal anvil has some similarities to the ds-DAC, as mentioned in the work of Dewaele et al and Khandarkhaeva et al tested several FIB machined toroidal anvils as second-stage anvils for the ds-DAC and concluded that the toroidal anvil showed greater stability in the assembly and more uniform pressure distribution in the sample cavity [65]. This result highlights the role of the T-DAC toroidal shape at high pressure and confirms its positive contribution.…”
Section: T-dacmentioning
confidence: 97%